2006
DOI: 10.1080/10426500500536572
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Reactions, and Anticancer Activity of Some 1,3,4-Thiadiazole/Thiadiazine Derivatives of Carbazole

Abstract: EgyptA novel method for the synthesis of 1,3,4-thiadiazole and 1,3,4-thiadiazine derivatives bearing a carbazole moiety is described. Carbazole was transformed into carbazole-9-thiocarbohydrazide in two steps. This compound was allowed to react with various electrophiles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…23,24 The thiyl radical fragment is very important for radical scavenging and anti-proliferative effects of S-BHT. As reported, a 1,3,4-thiadiazole moiety containing compounds have exhibited potential anticancer, 25,26 antitubercular 27 and antiulcer properties. 28 The aromaticity of 1,3,4-thiadiazoles was attributed to their potential as anticancer agent.…”
Section: Introductionmentioning
confidence: 75%
“…23,24 The thiyl radical fragment is very important for radical scavenging and anti-proliferative effects of S-BHT. As reported, a 1,3,4-thiadiazole moiety containing compounds have exhibited potential anticancer, 25,26 antitubercular 27 and antiulcer properties. 28 The aromaticity of 1,3,4-thiadiazoles was attributed to their potential as anticancer agent.…”
Section: Introductionmentioning
confidence: 75%
“…In recent years, interest in thiadiazines has increased because of the high biological activity and broad spectrum action of their derivatives . In addition, it has been reported that certain compounds bearing a thiadiazine nucleus possess significant antimicrobial and anticancer activities. Also, thiadiazines substitution on 3‐ position of coumarin nucleus has been reported to exhibit antioxidative/ antifungal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing the 1,3,4-thiadiazole nucleus have a wide range of pharmacological activities that include antimicrobial [ 31 ], antitubercular [ 32 ], anticancer [ 33 , 34 ] and antioxidant [ 35 ] properties.…”
Section: Introductionmentioning
confidence: 99%